Does artificial intelligence have a role in the IVF clinic?. Issue 3 (15th September 2021) - Chow, Darren J X; Wijesinghe, Philip; Dholakia, Kishan; Dunning, Kylie R
Abstract : Lay summary: The success of IVF has remained stagnant for a decade. The focus of a great deal of research is to improve on the current 30% success rate of IVF. Artificial intelligence (AI), or machines that mimic human intelligence, has been gaining traction for its potential to improve outcomes in medicine, such as cancer diagnosis from medical images. In this commentary, we discuss whether AI has the potential to improve fertility outcomes in the IVF clinic. Based on existing research, we examine the potential of adopting AI within multiple facets of an IVF cycle, including egg/sperm and embryo selection, as well as formulation of an IVF treatment regimen. We discuss both the potential benefits and concerns of the patient and clinician in adopting AI in the clinic. We outline hurdles that need to be overcome prior to implementation. We conclude that AI has an important future in improving IVF success.